(untitled) (Journal of Environmental Science and Natural Resources, 2017)
This research was conducted on the proximate composition, quality aspect and heavy metal concentration of sun-dried Silver Pomfret (Stromateus cinereus) and sun-dried Perch (Lates calcarifer) which were collected from local market of Cox‟s Bazar town. These sun-dried marine fishes were collected from the stock after first drying procedure. Organoleptically most of these sun-dried fishes were in „excellent‟ grade some were in „Good‟ grade. Crude Protein, Lipid, Moisture, Ash, TVB-N and TMA-N content (%) of sun-dried Silver Pomfret (Stromateus cinereus) was 32.25±1.50, 7.75±0.20, 39.59±0.34, 15.75±0.39, 85.68±1.60 and 8.41±0.37 respectively. Whereas in sun-dried Perch (Lates calcarifer) the content (%) of Crude Protein, Lipid, Moisture, Ash, TVB-N and TMA-N was 40.31±2.13, 5.03±0.55, 26.74±0.47, 11.50±0.26, 46.97±1.00 and 8.21±0.12 respectively. Heavy metal concentration i.e. Cd, Cr, Pb, Cu and Zn concentration (ppm) in sun-dried Silver Pomfret (Stromateus cinereus) was 0.68, 5.85, 8.43, 1.15, 24.93 ppm. Whereas heavy metal concentration (ppm) in sun-dried Perch (Lates calcarifer) was Cd 0.65 ppm, Cr 5.6 ppm, Pb 6.28 ppm, Cu 1.04 ppm, Zn 23.8 ppm. J. Environ. Sci. & Natural Resources, 10(1): 25-32 2017